Hubungan Kelelahan Kerja Dengan Tingkat Stres Perawat Pada Masa Pandemi Di Ruangan Isolasi Covid-19 - Mersi Ekaputri; Rohmi Fadhli; Meza Faslina (Universitas Malahayati Lampung, 2022)
ABSTRACT The Covid-19 pandemic has an impact on the work of nurses such as fatigue and work stress. Work stress is a tension that can cause physical, psychological, thought processes and emotional imbalances. The purpose of the study was to identify the relationship between work fatigue and the stress level of nurses during the pandemic in the Covid-19 isolation room, the research design was a descriptive correlation with a Cross Sectional approach. The population of all nurses in the Covid-19 Isolation Room at the Dumai City Hospital, which amounted to 36 nurses. Sampling technique with total sampling. The results showed that 50% of respondents experienced work fatigue in the tired category, more than half of 61.1% of respondents experienced moderate stress. The results of the statistical test showed that there was a relationship between work fatigue and the stress level of nurses during the pandemic in the Covid-19 isolation room (p = 0.009). Hospitals are expected to conduct direct field reviews related to the needs of nurses in the Covid-19 isolation room to maintain the performance of nurses in dealing with Covid-19 patients and are expected to provide rewards that are in accordance with the nurse's performance. Keywords: Covid-19, Fatigue, Stress, Nurse ABSTRAK Pandemi Covid-19 berdampak terhadap pekerjaan perawat seperti kelelahan dan stres kerja. Stres kerja merupakan ketegangan yang dapat menimbulkan ketidakseimbangan fisik,psikis, proses berfikir serta emosi. Tujuan penelitian untuk mengidentifikasi hubungan kelelahan kerja dengan tingkat stres perawat pada masa pandemi di ruangan isolasi Covid-19, desain penelitian deskripsi korelasi dengan pendekatan Cross Sectional. Populasi semua perawat di Ruangan Isolasi Covid-19 RSUD Kota Dumai yang berjumlah 36 perawat. Teknik pengambilan sampel dengan total sampling. Hasil penelitian didapatkan sebanyak 50% responden mengalami kelelahan kerja dengan kategori lelah, lebih dari separoh 61,1% responden mengalami stres tingkat sedang. Hasil uji statistik didapatkan terdapat hubungan kelelahan kerja dengan tingkat stres perawat pada masa pandemi di ruangan isolasi Covid-19 (p=0,009). Bagi pihak rumah sakit diharapkan melakukan tinjauan langsung ke lapangan terkait dengan kebutuhan perawat di ruang isolasi Covid-19 untuk menjaga kinerja perawat dalam menangani pasien Covid-19 serta diharapkan untuk memberikan reward yang sesuai dengan kinerja perawat Kata Kunci: Covid-19, Kelelahan, Stres, Perawat